La question des échelles en géohistoire. Les bureaux de la poste aux lettres du XVIIIe siècle à nos jours - Nicolas Verdier; Ludovic Chalonge (Cybergeo, 2018)
Starting from a practice of research that has been going back for years on the question of the use of scales in geohistorical works, this text offers a reflection on the plays of scale, as well as on the question of the MAUP (modifiable areal unit problem). By studying the history of the distribution of post offices in France during the last three centuries, it is a question of trying to place the questioning on the scale at the same level as those relating to space and time when studying social facts. In this framework, we offer to go through the idea of “scalable scalar profiles”, not only to insist on the necessary variations of scale in the analysis of spatio-temporal phenomena, but also to try to define evolutionary spatial templates to enable the widest possible understanding of processes.